“Don't Speak For Me”: Practicing Oral History amidst the Legacies of Conflict - Parr, Joy (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2010)
This article revisits claims that it is possible to ‘hare authority' in the practice of oral history, with particular reference to disturbed and disturbing sites, in which witnesses have been marked by difficult times and may not ‘now what they will tell' the interviewer. It also explores reflections by anthropologists, ethnographers, and translators on the politics of such relationships.